ANALISIS KUALITAS PELAYANAN LABORATORIUM MENGGUNAKAN METODE SERVQUAL (STUDI KASUS DI LABORATORIUM MANUFAKTUR TEKNIK INDUSTRI UNIVERSITAS BUANA PERJUANGAN KARAWANG) - Suryapranatha, Dicky; Saputra, Agung Andrean (Industry Xplore, 2025)
ML UBP is a laboratory that supports students' needs in the Manufacturing Process practicum course. The aim of this research is to determine the level of satisfaction and dimensions that are priorities for improvement in UBP ML services and to determine whether there is a relationship between student perceptions and student expectations for the services provided. The methods used are ServQual and correlation regression. The method for determining the number of samples in this study used the Slovin technique with a sample of 61 respondents. In this study the data was analyzed using the help of IBM SPSS Statistics 23 software. Based on the results of the analysis using the ServQual method to determine the results of service quality (Q) value for the Reliability dimension (0.856) , Responsiveness dimension (0.867), Assurance dimension (0.869), Empathy dimension (0.883) and Tangible dimension (0.891). The average value of all attributes is (0.873) which is still below 1, which means consumer satisfaction has not been met. then the dimension that is a priority for improvement is the Reliability dimension. And based on the Linear Regression Test, service quality does not affect student satisfaction with service.